2000
DOI: 10.1016/s0009-2541(00)00243-6
|View full text |Cite
|
Sign up to set email alerts
|

Major, trace element, and Nd, Sr and Pb isotope studies of Cenozoic basalts in SE China: mantle sources, regional variations, and tectonic significance

Abstract: Introduction. Transtension is a system of stresses that tends to cause oblique extension, i.e. combined extension and strike slip. Syn-volcanic transtensional deformations of the lithosphere may provide two possible scenarios for control of magmatic processes. One scenario assumes ascending sub-lithospheric melts that mark the permeable lithosphere in a transtension area without melting of the lithospheric material; products of volcanic eruptions in such a zone show only the sub-lithospheric mantle material; c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
278
1
4

Year Published

2005
2005
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 465 publications
(297 citation statements)
references
References 49 publications
14
278
1
4
Order By: Relevance
“…The Cenozoic volcanic rocks in SE and NE China show different isotopic compositions due to varied SCLM compositions beneath the two regions (e.g., Zou et al, 2000). SE China is underlain by relatively young, middle to late Proterozoic continental lithosphere, whereas NE China is underlain by Archaean to early Proterozoic continental lithosphere (e.g., Chen and Jahn, 1998).…”
Section: Implications For the Genesis Of Eastern China Basaltsmentioning
confidence: 99%
See 2 more Smart Citations
“…The Cenozoic volcanic rocks in SE and NE China show different isotopic compositions due to varied SCLM compositions beneath the two regions (e.g., Zou et al, 2000). SE China is underlain by relatively young, middle to late Proterozoic continental lithosphere, whereas NE China is underlain by Archaean to early Proterozoic continental lithosphere (e.g., Chen and Jahn, 1998).…”
Section: Implications For the Genesis Of Eastern China Basaltsmentioning
confidence: 99%
“…The volcanic rocks are predominantly basalts and are thought to have been derived from variable mantle sources (Chung et al, 1994;Fan and Hooper, 1991;Zhou and Armstrong, 1982;Zou et al, 2000). It is commonly accepted that basalts in SE China originated from a mixed source involving asthenospheric mantle and EM2, and that those in NE China were derived from a mixed source of asthenospheric mantle and EM1 (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is noted that the MORB normalized trace element patterns for these samples (Fig. 6) are similar to those of Late Cenozoic basalts in Southeast China (Peng et al, 1986;Flower et al, 1992;Liu et al, 1994;Qi et al, 1994;Chung et al, 1994Chung et al, , 1995Zou et al, 2000;Ho et al, 2003). The MORB-normalized multielement diagrams display small differences, for example the Luokou mafic rocks exhibit weak Rb positive anomalies and minor Ba negative anomalies, while the Tianxinggang rocks show weak Ba positive anomalies and minor Rb negative anomalies.…”
Section: Major and Trace Element Datamentioning
confidence: 51%
“…Irvine and Baragar (1971). The fields of Cretaceous mafic rocks and basalts (e.g., Lan et al, 1995;Lapierre et al, 1997;Li and McCulloch, 1998;Xiong et al, 2003;Xie et al, 2006) and Late Cenozoic basalts (e.g., Flower et al, 1992;Qi et al, 1994;Liu et al, 1994;Zou et al, 2000) in Cathaysia Block are shown for comparison. …”
Section: Major and Trace Element Datamentioning
confidence: 99%